Removing endogenous tau does not prevent tau propagation yet reduces its neurotoxicity. (4th November 2015) - Wegmann, Susanne; Maury, Eduardo A; Kirk, Molly J; Saqran, Lubna; Roe, Allyson; DeVos, Sarah L; Nicholls, Samantha; Fan, Zhanyun; Takeda, Shuko; Cagsal‐Getkin, Ozge; William, Christopher M; Spires‐Jones, Tara L; et al.
Abstract: In Alzheimer's disease and tauopathies, tau protein aggregates into neurofibrillary tangles that progressively spread to synaptically connected brain regions. A prion‐like mechanism has been suggested: misfolded tau propagating through the brain seeds neurotoxic aggregation of soluble tau in recipient neurons. We use transgenic mice and viral tau expression to test the hypotheses that trans‐synaptic tau propagation, aggregation, and toxicity rely on the presence of endogenous soluble tau. Surprisingly, mice expressing human P301Ltau in the entorhinal cortex showed equivalent tau propagation and accumulation in recipient neurons even in the absence of endogenous tau. We then tested whether the lack of endogenous tau protects against misfolded tau aggregation and toxicity, a second prion model paradigm for tau, using P301Ltau‐overexpressing mice with severe tangle pathology and neurodegeneration. Crossed onto tau‐null background, these mice had similar tangle numbers but were protected against neurotoxicity. Therefore, misfolded tau can propagate across neural systems without requisite templated misfolding, but the absence of endogenous tau markedly blunts toxicity. These results show that tau does not strictly classify as a prion protein. Synopsis: Prions are propagated by corrupting endogenous homologous molecules, and this leads to their toxicity. By contrast, transgenic human tau protein can propagate from the entorhinal cortex to neurons in the dentate gyrus even in tau knockout (Mapt 0/0 ) mice. However, neuronal death caused by mutant human P301Ltau overexpression is reduced in the absence of endogenous tau despite similar levels of neurofibrillary tangle (NFT) formation. Tau propagation to synaptically connected neurons occurs in the absence of endogenous tau. The neurotoxicity caused by accumulation of human mutant tau and NFTs is largely rescued by the absence of endogenous mouse tau. Tau thus shows some (but not all) characteristics of prionoid proteins and may have a role in neurotoxicity. Abstract : While endogenous tau is needed for mutant tau‐mediated neurotoxicity, it is not required for misfolded tau propagation across synaptically connected neurons thus supporting the notion that tau does not strictly classify as a prion protein.